Effects of guideline directed medical therapy on secondary mitral regurgitation. (3rd October 2022) - Spinka, G; Bartko, P E; Heitzinger, G; Prausmueller, S; Winter, M P; Arfsten, H; Strunk, G; Rosenhek, R; Kastl, S; Hengstenberg, C; Pavo, N; Huelsmann, M; et al.
Abstract: Background: Guideline directed medical therapy (GDMT) is the recommended initial treatment for secondary mitral regurgitation (SMR), however supported by only little comprehensive evidence. This study therefore sought to assess the effect of GDMT titration on SMR and to identify specific substance combinations able to reduce SMR severity. Methods: We included 261 patients who completed two visits with an echocardiographic exam available within one month at each visit. After comprehensively defining GDMT titration as well as SMR reduction, logistic regression analysis was applied in order to assess the effects of overall GDMT titration and specific substance combinations on SMR severity. Results: SMR severity improved by at least one degree in 39.3% of patients with subsequent titration of GDMT and was accompanied by reverse remodelling and clinical improvement. The effects of GDMT titration were significantly associated with SMR reduction (adj. OR 0.31, 95% CI 0.13–0.71, P=0.006). Moreover, ARNI as well as the combined dosage effects of (i) renin angiotensin system inhibitors (RASi) and mineralocorticoid-receptor antagonists (MRA), (ii) betablockers (BB) and MRA, as well as (iii) RASi, BB, and MRA were all significantly associated with SMR improvement (P<0.001 for all). Conclusions: The present study provides comprehensive evidence for the effectiveness of contemporary GDMT to specifically improve SMR. Our data indicates that GDMT titration conveys a threefold increased chance of reducing SMR severity. Moreover, the dosage effects of ARNI, as well as the combination of RASi and MRA, BB and MRA, and all three substances in aggregate are able to significantly improve SMR. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): FWF - Austrian Science Fund